Effect of pH and magnesium on colour development and anthocyanin accumulation in tuberose florets - Muriithi, Alice Nakhumicha; WAMOCHO, L. S.; NJOROGE, J. B. M. (African Crop Science Conference Proceedings, Vol. 9. pp. 227 - 234, 2009)
Anthocyanins are a group of plant pigments responsible for colors ranging from red to violet and blue. Anthocyanins are pigments that accumulate in the vacuoles of plant epidermal cells. Chroma and hue are dependent on conditions inside and outside the vacuoles. Also conditions within the vacuole that facilitate formation of complexes with several metal ions. The aim of this study was to examine changes in accumulation of anthocyanins and the resultant colour in tuberose (Polianthes tuberosa Linn.) after application of amendments to the soil. Treatments were applied six weeks after planting as a top dress. Magnesium was given as magnesium nitrate and nitrogen was given as calcium ammonium nitrate CAN was neutral and ammonium sulphate (AS) was acidic. Soil and plant tissues were analysed every two weeks for nitrogen, phosphorus, potassium, magnesium, and pH. Colour was determined using a photoelectric tri-stimulus colorimeter and expressed in CIE L*a*b* colour space coordinates. In addition, chlorophyll and anthocyanins in the florets were quantified. The amendments lowered the soil pH, especially for the AS and CAN. However, chroma and hue values as determined by the space coordinates, as well as the concentrations of anthocyanins in the floret, were not significantly linked to the soil pH following the amendments. Equally, the tissue elements and chlorophyll contents were similar between the amendments. The results of this study show that supplying magnesium through fertiliser application to the soil does not necessarily increase accumulation of Mg in tissues, and may ultimately not lead to accumulation of anthocyanins.
Keywords: Chroma; hue; metal complexes; Polianthes tuberosa; plant pigments